Tinjauan Terhadap Strategi Manajemen Perpustakaan di SMA Negeri 3 Salatiga: Peningkatan Mutu Pelayanan dan Minat Baca - Naoura; Soliha, Silfana Wiwit; Hidaya, Almer Samantha (Nur Science Institute, 2025)
Libraries in educational settings play a crucial role in improving the quality of education, yet their management often faces significant challenges. This study aims to identify and analyze the management strategies implemented at the SMA Negeri 3 Salatiga library to enhance service quality and promote reading interest. Adopting a qualitative case study approach, this research collected data through in-depth interviews with two experienced librarians and direct observation of library operations. The results indicate that managerial strategies, such as proactive leadership and periodic performance evaluations through annual meetings, have a significant positive contribution to the quality of library services. These strategies correlate with an increased reading interest and literacy among students. Despite facing challenges like limited fund allocation and human resources, the library continues to pursue improvements through structured evaluations to ensure the sustainability of its strategies. This research concludes that a well-structured management strategy is vital for optimizing library services and fostering a reading culture in a high school environment.